Experimental manipulation of reproductive tactics in Seba's short-tailed bats: consequences on sperm quality and oxidative status. Issue 6 (23rd March 2019) - Meniri, Magali; Gohon, Florence; Gning, Ophélie; Glauser, Gaétan; Vallat, Armelle; Fasel, Nicolas J; Helfenstein, Fabrice
Abstract: To reproduce, males have to fertilize the female's eggs, sometimes in competition with ejaculates of other males. In species where males display alternative reproductive tactics, whereby territorial males secure mating and non-territorial males have to sneak copulations, the latter might be expected to invest relatively more resources towards sperm quality compared with the territorial males. Sperm cells are especially vulnerable to oxidative stress, which reduces male fertility. Therefore, antioxidant resources are expected to modulate sperm quality, and might be allocated differently between reproductive tactics. To test the link between reproductive tactics, redox profile and sperm quality, we experimentally induced changes in the reproductive tactics of 39 captive males Seba's short-tailed bats Carollia perspicillata . We monitored the blood and ejaculate oxidative balance, and the sperm quality before, 7 days and 21 days after the manipulation of reproductive tactic. Although ejaculates' oxidative damage was negatively related to sperm velocity, males exhibited similar blood and ejaculates redox profiles and similar sperm quality, regardless of their reproductive tactic. Possibly, these results arise as a consequence of some constraints having been lifted during the experiment. Our results also suggest that, in Seba's short-tailed bats, the expression of alternative reproductive tactics is not subjected to strong oxidative constraints. Furthermore, our results could reflect an absence of trade-off between pre- and post-copulatory traits in harem males, as they could be selected to invest both in female attraction and sperm quality, as a consequence of their inability to fully monopolize females.